2022
DOI: 10.1123/ijspp.2021-0484
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hormones, Morphological Characteristics, and Physical Performance in Elite Soccer Players

Abstract: Purpose: To determine the relationship between gastrointestinal hormones (leptin, glucagon-like peptide-1), ghrelin, cholecystokinin, peptide YY, morphological characteristics, and physical performances in elite soccer players. Methods: Q2 Twenty-two elite male soccer players (age = 23.1 [2.7] y, height = 177.0 [0.1] cm, weight = 70.2 [2.9] kg, body mass index = 22.1 [1.8] kg/m2) completed 3-day food records each week during the 5-week training period. Blood samples were drawn after an overnight fast before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…It seems reasonable to suggest that training program during competition phase, more than preparation phase, can improve significantly on body compositions and therefore on muscle tone in relation to training program load. In agreement with the current results, Salhi et al (27) showed that chronic football training has an effect on body composition and hormones associated with the process of physiological regulation of food consumption. In fact, soccer training might alter body composition (body composition, BMI, and BF%) in elite male soccer players by decreasing leptin levels and increasing GLP-1 levels.…”
Section: Discussionsupporting
confidence: 93%
“…It seems reasonable to suggest that training program during competition phase, more than preparation phase, can improve significantly on body compositions and therefore on muscle tone in relation to training program load. In agreement with the current results, Salhi et al (27) showed that chronic football training has an effect on body composition and hormones associated with the process of physiological regulation of food consumption. In fact, soccer training might alter body composition (body composition, BMI, and BF%) in elite male soccer players by decreasing leptin levels and increasing GLP-1 levels.…”
Section: Discussionsupporting
confidence: 93%